25-Hydroxyvitamin D status does not affect energy metabolism among young, healthy, non-obese adults: a metabolic chamber study - Zhang, Lin; Cai, Haogang; Bai, Xiaorong; Xiao, Wensheng; Cao, Zhen-Bo; Zhang, Yang (Frontiers in Endocrinology, 2024)
Purpose: There is a general consensus that an inverse relationship exists between vitamin D status and body mass index (BMI) in overweight and obese individuals, leading to the hypothesis that vitamin D deficiency may contribute to the development of unfavorable metabolic phenotypes. However, evidence from non-obese adults remains limited. This study measured energy metabolism in non-obese adults using a metabolic chamber and explored its association with vitamin D status. Methods: Sixty-nine healthy adults (mean age = 22.8 years, mean BMI = 20.7 kg/m2) participated in this cross-sectional study. Participants were categorized into vitamin D-deficient, insufficient, and sufficient groups based on the Chinese classification for total 25(OH)D levels (WS/T 677–2020). They performed typical daily activities in a metabolic chamber, where their baseline lipid profile, 24-hour energy expenditure, and substrate oxidation were measured. Results: A two-way ANOVA (seasonality × 25(OH)D) revealed no statistically significant differences in total energy expenditure, resting energy expenditure, sleeping energy expenditure, walking energy expenditure, carbohydrate oxidation rate, or fat oxidation rate among the three groups (p > 0.05). These results remained consistent even after adjusting for fat-free mass. Although statistically significant correlations were found between 25(OH)D status and certain lipid profile markers (i.e., total cholesterol, high-density lipoprotein, and free fatty acid) (p < 0.05), these correlations were weak, with Pearson’s correlation coefficients below 0.3. Conclusions: Total 25(OH)D status does not affect energy metabolism in young, healthy, non-obese adults. Along with existing evidence, this suggests that low 25(OH)D status is more likely a consequence of unfavorable metabolic phenotypes rather than a contributing factor.